2020
DOI: 10.1037/abn0000517
|View full text |Cite
|
Sign up to set email alerts
|

The role of affect in the maintenance of binge-eating disorder: Evidence from an ecological momentary assessment study.

Abstract: consistent with affect regulation models of eating pathology and suggest that binge-eating episodes may be maintained through a process of negative reinforcement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
86
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 38 publications
10
86
2
Order By: Relevance
“…Binge eating may be used as a way to momentarily increase PA in individuals with BED. Consistently, in a recent EMA study of adults with BED, trajectories of PA surrounding binge eating showed that, on average, PA decreased prior to binge eating and stabilized following binge eating, providing evidence for a PA‐enhancing effect of binge eating in BED (Schaefer et al, 2020).…”
Section: Anhedonia As a Maintenance Factor For Bedmentioning
confidence: 56%
See 1 more Smart Citation
“…Binge eating may be used as a way to momentarily increase PA in individuals with BED. Consistently, in a recent EMA study of adults with BED, trajectories of PA surrounding binge eating showed that, on average, PA decreased prior to binge eating and stabilized following binge eating, providing evidence for a PA‐enhancing effect of binge eating in BED (Schaefer et al, 2020).…”
Section: Anhedonia As a Maintenance Factor For Bedmentioning
confidence: 56%
“…Although little research has explicitly examined the role of anhedonia in binge‐eating disorder (BED), some work has investigated the more general and dimensional role of PA. Consistent with affect regulation models of eating pathology, evidence indicates that low PA is an antecedent of binge‐eating episodes among individuals with BED (Schaefer et al, 2020). Baseline PA dynamics have also been found to predict BED treatment outcomes, including changes in binge‐eating frequency and weight (Mason et al, 2020; Mason et al, in press).…”
Section: Introductionmentioning
confidence: 88%
“…For example, irritability is linked to starvation in anorexia nervosa (AN; Sidiropoulos, 2007), and fear (e.g., fear of weight gain) is a core symptom in EDs (Levinson, Brosof, Ma, Fewell, & Lenze, 2017). Shame (i.e., negative internal, global, and stable feelings about oneself; Tangney & Dearing, 2003) and guilt (i.e., internal negative feelings about a specific behavior; Tangney & Dearing, 2003) have also been linked to ED behaviors such as binge eating (Schaefer et al, 2020). However, no research has incorporated many unique NA states in one integrated model to understand the complex associations across NA and a variety of ED symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…A total of eight NA items were included in EMA AN (Engel et al, 2013), 11 NA items in EMA BN (Smyth et al, 2007), and 20 NA items in EMA BED (Peterson et al, 2019). Reliability estimates (coefficient α) for the selected NA items in each study ranged from good (.80 in EMA BED) to excellent (.92 for EMA AN and BN; Engel et al, 2013; Schaefer et al, 2019; Smyth et al, 2007). Seven NA items were used in all three studies and were subsequently used for the affective dynamics calculations in the current study: afraid, angry at self, ashamed, disgusted, dissatisfied with self, nervous, and sad.…”
Section: Methodsmentioning
confidence: 96%